ИСЛЕДОВАНИЕ ИЗМЕНЕНИЯ КАЧЕСТВЕННЫХ ПОКАЗАТЕЛЕЙ РАСТИТЕЛЬНОГО МАСЛА И ПРОДУКТОВ ЕГО ПЕРЕРАБОТКИ - Саидов Абди.; Утаева Гузал Нурбаевна (Journal of new century innovations, 2024)
Annotation. To obtain solid fats and fatty acids with a sufficiently high melting point, the process of hydrogenation of liquid fats is used, in which the reaction of addition of additional hydrogen atoms to the unsaturated bonds of liquid triglycerides, which make up the bulk of vegetable oils, occurs, and the physical properties of fats change.